Scalar cross-relaxation detected in the NOESY spectra of oxazolidines and thiazolidines - Claridge, T; Moloney, M; Odell, B; Kuprov, I; Panduwawala, T; Josa-Culleré, L (American Chemical Society, 2016)
Anomalous cross-peaks observed in the NOESY spectra of 2,4-disubstituted thiazolidines and oxazoli-dines that cannot be attributed to classical dipolar NOE or chemical exchange peaks have been investi-gated experimentally and computationally and shown to arise from scalar cross-relaxation of the first kind (SCRFK). This process is stimulated by the relatively slow modulation of scalar couplings, and for the systems studied arises from slow on-off proton exchange of the amino nitrogen, a process influenced by solution temperature, acidity and concentration. The mechanism is likely to be significant for many systems in which proton exchange occurs on the millisecond timescale, and misinterpretation of these cross-peaks may lead to erroneous conclusions should their true origins not be recognised.